Щелкунчик и мышиный король - Гофман Эрнст Теодор Амадей (Школьная библиотека, 2004)
Экземпляры: ф.3 (2006) / Инвентарный номер: 48495 / Цена: / Сис.шифр: 84(4Гем)-44 / Авт.знак: Г 74 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-44